PENDETEKSIAN POTENSIAL HOTSPOT DATA SATELIT DAN GROUND CHECK BERBASIS ALGORITMA CLUSTERING K-MEANS - Rony Teguh; Fitri Handayani; Ariesta Lestari (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2021)
In this study, these is a grouping of hotspot data to determine the pattern of areas that are prone and not prone to hotspots in Pulang Pisau Regency in the last 5 years, The dataset starting from 2015-2019. We use the hotspot data for grouping process uses the K-Means clustering algorithmin this computation. After the clustering results are obtained, then the data will be validated using ground check data to determine the accuracy of the clustering results. The validation process is carried out by comparing the coordinates of the clustered data with ground check data at the same location to find out whether the clustering results are really accurate